ضعف عمق الوساطة المالية شواهد من الجهاز المصرفي التجاري العراقي ( الجزء الأول) (المجلة العراقية للعلوم الاقتصادية, 2018)
Iraq 's economic growth and financial development are driven in alarge extend by the performance of oil sector.The financial sector's contribution to overall economic activity is still very low in Iraq.The share of the banking and insurance sector in GDP accounted as an averge of ( 1,3) percent between(2007-2012)The financial intermediation dominated by the commercial banking system face a significant weakness, when looking at its practices.Deposits ,credit ,assets,capital remain low by international standards, and by comparison with a large number of Arab commercial banks.